EFFECT OF COLD WATER BATH COMBINED WITH STRETCHING AND SWEDISH MASSAGE ON CHANGES IN LACTATE AND OXYGEN LEVELS IN THE FINGERTIPS - Jaronsukwimon , Nutdanai; Wongdontree , Kittisak (Academic Journal of Thailand National Sports University, 2023)
The purpose of this research was to study the effects of cold water bathing combined with stretching and Swedish massage on changes in sports physiology. of students Faculty of Sports and Health Sciences National Sports University Chonburi Campus, male, aged between 18 - 22 years, 30 people, divided into 3 groups: a control group (sitting still) of 10 people, an experimental group (cold water bathing with stretching) 10 people, and a group (massage). 10 subjects, all three groups were measured for the physiological variable, lactic acid level in the blood. The fingertip blood oxygen values were 4 times before the 400 m run in the first lap, immediately after the first lap, immediately after the recovery in the 3 groups for a period of 30 minutes and immediately after the second lap, which It’s the final round immediately. The differences in blood lactic acid levels and blood oxygen levels were compared in the three groups in four sessions: before the first 400 m race, immediately after the first lap, and periodically after recovery in the three groups. Time of 30minutes immediately and immediately after the second, which is the final lap. Basic statistical analysis, mean, standard deviation, and mean difference were compared by statistical analysis of the data used for one-way ANOVA analysis. The statistical significance was also determined at the .05 level. The research results were found that showed that A 30-minute recovery method using cold water baths combined with stretching or Swedish massage. was able to reduce the amount of lactate in the blood more than the 30-minute sitting method with a statistically significant difference at the .05 level and the estimated post-restoration plasma oxygen value. By the method of soaking in cold water together with stretching the muscles. Swedish massage and sitting for 30 minutes were not significantly different at the .05 level.